1996
DOI: 10.1056/nejm199612123352403
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Abnormalities in People Heterozygous for Hemochromatosis

Abstract: The phenotype of persons heterozygous for hemochromatosis differs from that of normal subjects, but complications due to iron overload alone in these heterozygotes are extremely rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
181
0
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(194 citation statements)
references
References 26 publications
(25 reference statements)
7
181
0
6
Order By: Relevance
“…35,36 The mean serum iron concentrations, ferritin levels and transferrin-saturation values were higher in heterozygous subjects than in normal ones, as were mean haemoglobin levels and mean corpuscular volume. The prevalence of iron deficiency anaemia was lower in women who carried HFE mutations.…”
Section: Discussionmentioning
confidence: 93%
“…35,36 The mean serum iron concentrations, ferritin levels and transferrin-saturation values were higher in heterozygous subjects than in normal ones, as were mean haemoglobin levels and mean corpuscular volume. The prevalence of iron deficiency anaemia was lower in women who carried HFE mutations.…”
Section: Discussionmentioning
confidence: 93%
“…In our control group we included heterozygote siblings of individuals with haemochromatosis because earlier studies have shown that heterozygotes for HFE mutations have only slightly higher iron indices than wild-types and are not affected by the morbidities attendant with homozygosity [16,36], and do not exhibit abnormalities in insulin resistance or secretion [37]. The study of mouse models of haemochromatosis also suggests that iron overload and not the HFE mutations per se are responsible for the glucose homeostasis phenotype [15], and the heterozygous controls in this study did not have elevated serum ferritin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterised by an inappropriately increased absorption of dietary iron that leads to excess iron deposition in various tissues and organs [24]; it is inherited as an autosomal recessive trait linked to the major histocompatibility complex on the short arm of chromosome 6. Although severe iron overload is typical of homozygous hemochromatosis, minor modifications of serum iron, transferrinsaturation and serum ferritin can also be observed in a fraction of heterozygotes, but very rarely they give rise to complications [6]. However, the mild modifications of iron status induced by heterozygous hemochromatosis can influ-ence the severity and clinical evolution of heterogeneous conditions such as hepatitis [32], porphyria cutanea tarda [27] and cardiovascular disease [26].…”
Section: Introductionmentioning
confidence: 99%